Implementasi Pembelajaran Kursus Komputer Desain Grafis di Lembaga Pendidikan Dan Pelatihan Siap Kerja (LPPSK) EMC Informatika Kudus - Nida, Khoirin; Sutarto, Joko (Peneliti.net, 2024)
This research was carried out as an effort to help people become competent human resources and have the skills to be able to compete in the world of work through computer graphic design courses. The aim of this research is to describe the implementation of computer graphic design course learning including planning, implementation and evaluation as well as supporting and inhibiting factors. This research uses a descriptive qualitative approach with research subjects including the head of LPPSK, instructors and course participants. The data sources used are primary data and secondary data. Data collection techniques through observation, interviews and documentation. Data validity techniques use source triangulation and technical triangulation. Data analysis techniques are carried out by collecting data, reducing data, presenting data and drawing conclusions. The results of this research show that: (1) learning implementation includes planning consisting of learning objectives, teaching materials, students, instructors, facilities and infrastructure as well as time allocation. The implementation includes learning materials, learning methods, learning media, creating communication and providing motivation. In evaluation through evaluation of results, process and end. (2) supporting factors, namely clear learning objectives, teaching materials in accordance with the SKKNI and DUDI curriculum, competent instructors, appropriate learning media and methods, supporting facilities and infrastructure, creating good communication and providing motivation, students' ability to absorb learning material, there are competency exam questions. Meanwhile, the inhibiting factors are the lack of instructors, time management and the weather. The conclusion of this research is that the implementation of graphic design computer course learning has been carried out well. The researcher's suggestion is to recruit instructors and instructors to be more enthusiastic in creating communication and providing motivation to students.